SOCIOCULTURAL CHANGE OF SCIENTIFIC COGNITION - Скиба, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article deals with the research of sociocultural factors influence on the process of scientific cognition.